2001
DOI: 10.1159/000047856
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic in vivo Distribution of Bone Marrow-Derived Mesenchymal Stem Cells after Infusion

Abstract: Bone marrow-derived mesenchymal stem cells (MSCs) have the potential to differentiate along different mesenchymal lineages including those forming bone, cartilage, tendon, fat, muscle and marrow stroma that supports hematopoiesis. This differentiation potential makes MSCs candidates for cell-based therapeutic strategies for mesenchymal tissue injuries and for hematopoietic disorders by both local and systemic application. In the present study, rat marrow-derived MSCs were ex vivo culture-expanded, labeled with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
633
5
11

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 870 publications
(699 citation statements)
references
References 32 publications
50
633
5
11
Order By: Relevance
“…Prockop considered paradigm one to be highly unlikely to account for MSC beneficial effects in lung diseases. Although intravenously administered MSCs are initially "trapped" in the lung, imaging studies have failed to document significant long-term pulmonary engraftment of MSCs (74,75). In the lung, he believes that paradigm three is most likely, and the identification of factors secreted by MSCs may enable the development of novel specific protein-or small molecule-based therapies for ALI.…”
Section: Session 2: Embryonic Stem Cells Ipscs and Lung Regenerationmentioning
confidence: 99%
“…Prockop considered paradigm one to be highly unlikely to account for MSC beneficial effects in lung diseases. Although intravenously administered MSCs are initially "trapped" in the lung, imaging studies have failed to document significant long-term pulmonary engraftment of MSCs (74,75). In the lung, he believes that paradigm three is most likely, and the identification of factors secreted by MSCs may enable the development of novel specific protein-or small molecule-based therapies for ALI.…”
Section: Session 2: Embryonic Stem Cells Ipscs and Lung Regenerationmentioning
confidence: 99%
“…infusion mostly in lungs and secondarily in liver and other organs. 44 More detailed studies in three baboons (two using autologous and one allogeneic MSC) and using the green fluorescent protein retroviral construct showed that gastrointestinal tissues harboured high concentrations of transgene per microgram of DNA. Additional tissues including kidney, lung, liver, thymus, and skin were also found to contain relatively high amounts of DNA equivalents.…”
Section: Fate Of Transplanted Mscs In Vivomentioning
confidence: 99%
“…Our approach of delivering human MSCs intraperitoneally may have helped minimise access of these cells to the CNS [2]. Certainly using either antibody staining for human nuclear antigen or the fluorescence of GFP-labelled cells we found barely detectable levels of CNS infiltration, and yet observed a pronounced therapeutic impact of these cells on EAE severity.…”
mentioning
confidence: 92%